Enhanced RNAi does not provide efficient innate antiviral immunity in mice - Kulmann, Marcos Iuri Roos; Taborska, Eliska; Benköova, Brigita; Palus, Martin; Drobek, Ales; Horvat, Filip; Pasulka, Josef; Malik, Radek; Salyova, Eva; Hönig, Vaclav; Pellerova, Michaela; Borsanyiova, Maria; et al. (Nucleic acids research, 2025)
In RNA interference (RNAi), long double-stranded RNA is cleaved by the Dicer endonuclease into small interfering RNAs (siRNAs), which guide degradation of complementary RNAs. While RNAi mediates antiviral innate immunity in plants and many invertebrates, vertebrates have adopted a sequence-independent response and their Dicer produces siRNAs inefficiently because it is adapted to process small hairpin microRNA precursors in the gene-regulating microRNA pathway. Mammalian endogenous RNAi is thus a rudimentary pathway of unclear significance. To investigate its antiviral potential, we modified the mouse Dicer locus to express a truncated variant (DicerΔHEL1) known to stimulate RNAi and we analyzed how DicerΔHEL1/wt mice respond to four RNA viruses: coxsackievirus B3 and encephalomyocarditis virus from Picornaviridae; tick-borne encephalitis virus from Flaviviridae; and lymphocytic choriomeningitis virus (LCMV) from Arenaviridae. Increased Dicer activity in DicerΔHEL1/wt mice did not elicit any antiviral effect, supporting an insignificant antiviral function of endogenous mammalian RNAi in vivo. However, we also observed that sufficiently high expression of DicerΔHEL1 suppressed LCMV in embryonic stem cells and in a transgenic mouse model. Altogether, mice with increased Dicer activity offer a new benchmark for identifying and studying viruses susceptible to mammalian RNAi in vivo.
Keywords: viry klíšťové encefalitidy; virus lymfocytární choriomeningitidy; Encephalomyocarditis virus; DEAD-box RNA Helicases; RNA interference; Immunity, Innate; myši inbrední C57BL; DEAD-box RNA-helikasy; RNA Interference; Mice; Encephalitis Viruses, Tick-Borne; přirozená imunita; ribonukleasa III; Animals; virus encefalomyokarditidy; zvířata; Ribonuclease III; myši; malá interferující RNA; RNA, Small Interfering; Mice, Inbred C57BL; Lymphocytic choriomeningitis virus